THE EFFECT OF FORMULATION HUMIC SUBSTANCE AND Trichoderma sp TO INCREASE PRODUCTION AND GROWTH OF CORN (Zea Mays L.) - Ruly Eko Kusuma Kurniawan (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2017)
Research to determine of formulation humic substance and Trichoderma sp to increase the production and growth of corn (Zea mays, L). This research was conducted by extracting humic substance with fractionation organic matter method from cattle manure organic material. Trichoderma sp grow on corn medium and harvested after reaching a density of 1015 cfu. Created this compound formulation with mixing humic substance and Trichoderma sp. Indicator plant with F1 sweet corn Jago varieties. Application used humic substance in range 8%, 16%, and 32% on the recommended use NPK fertilizer for corn, as well as control without humic substance. The result showed application use  8% humic substance most good for plant growth and harvest. Additionally, nutrient uptake NPK fertilizer efficiency is increased and more effective than control and use of the formulation 16% and 32% humic substance.